Brewery Tourism in Niterói/RJ: A contribution to the valorization of the tourist destination - Rosa, Lélio Galdino; Minasse, Maria Henriqueta Sperandio Garcia Gimenes; Oliveira, Sérgio Domingos de; Cunha, Monique Laurencia dos Santos (Seven Editora, 2023)
According to the Ministry of Agriculture, Livestock and Supply (MAPA) in 2020, the production of craft beer in Brazil showed considerable growth, reaching the number of 1383 producing units. The state of Rio de Janeiro follows this growth, and the number of breweries registered and operating in the market increased significantly from 2017 to 2020, presenting a growth of 21.4% in this period. The city of Niterói, located in the metropolitan region of Rio de Janeiro, emerges in the Brazilian scenario as one of the municipalities with the best human development index (HDI), standing out in the national scenario, as well as in the production of craft beers. However, it is believed that, despite the competition, there is still room for investments in the area, since demand has also risen, coupled with the fact that consumers are increasingly demanding and want better quality products, especially when referring to special beers. We highlight the binomial welcome and reception of visitors with the appreciation of beer, placing them as an identity asset of a locality and its people. Still, the events in which beer complements this celebration, as well as identify that the joint participation of the community and visitors or tourists is increasingly common. In order to offer products and services that are compatible with the growing demand of this public, several routes and itineraries with the beer theme appear in Brazil. In this way, the planning, organization and training of brewing enterprises is fundamental to achieve and even exceed the expectations of its consumers. Taking into account these characteristics, this research aimed to propose the organization of routes or paths of beer tourism in the city of Niterói. To develop it, we opted for the methodology of descriptive, bibliographic and documentary study, concomitant with the netgraphic research. The research is characterized as exploratory, requiring data collection in order to trace possible brewing routes in Niterói and their respective locations through the use of forms adapted from INVTur - Inventory of Tourism Offer, of the Ministry of Tourism. Thus, a total of 78 enterprises located in Niterói were identified. These, in turn, were subdivided into 26 home microbreweries, 18 brewing bars, 27 gypsy microbreweries and 7 own breweries. From the observations presented, the research resulted in the proposition of three itineraries, called Brewing Paths, aligning them with Niemeyer, consecrated local tourist attraction, namely: Ocean Way, which includes three breweries with factory; Icaraí Way, composed of the Biergarten and two beer bars; and the Guanabara Way, which includes Vila Cervejeira and two breweries with factories. In possession of this information, a Brewery Tourist Map of Niterói was created, and it was made available to the competent bodies of Niteroienses. It is noteworthy, however, that these paths are organizational proposals, and the sequence or punctual options of visits should be decided by specialized tourism agencies or even by the people or groups themselves interested in the theme. DOI:https://doi.org/10.56238/alookdevelopv1-095